2020
DOI: 10.1103/physrevd.102.016005
|View full text |Cite
|
Sign up to set email alerts
|

Production of the predicted K*(4307) in B decays

Abstract: In this work we study the production of K Ã ð4307Þ in B decays by determining the J=ψπ þð0Þ K 0 and J=ψπ − K þ invariant mass distributions of the processes B þ → J=ψπ þ π 0 K 0 and B þ → J=ψπ þ π − K þ , respectively. Such K Ã ð4307Þ has been recently predicted as a three-body state originating from the dynamics involved in the KDD Ã system, with the KD subsystem forming the D Ã s0 ð2317Þ in isospin 0, and the DD Ã subsystem generating the Xð3872Þ in isospin 0 and the Z c ð3900Þ in isospin 1. The hidden charm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Studies of further properties of * (4307) can be found in Refs. [36,37]. Figure 2 shows the results for the → and → transitions with ( ) = 1/2 (1/2 + ) and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of further properties of * (4307) can be found in Refs. [36,37]. Figure 2 shows the results for the → and → transitions with ( ) = 1/2 (1/2 + ) and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The fact of having an important (3900) molecular component in the wave function of * (4307) indicates that the state can also easily decay to a channel like / . In this way, the reconstruction on the / invariant mass in processes involving these particles in their final states can be a promising way of observing this * (4307) [29].…”
Section: Formalism and Resultsmentioning
confidence: 99%
“…Studies of further properties of 𝐾 * (4307) can be found in Refs. [36,37]. Figure 2 shows the results for the 𝑁 𝑋 → 𝑁 𝑋 and 𝑁 𝑍 𝑐 → 𝑁 𝑍 𝑐 transitions with 𝐼 (𝐽 𝑃 ) = 1/2 (1/2 + ) and Fig.…”
Section: Resultsmentioning
confidence: 99%